(untitled) (Proceedings of Southern Federal University. Philology, 2012)
Minina A. A. Keywords: sociocultural competence, knowledge, skills, cross-cultural communication The article is devoted to the problem of controlling sociocultural competence of non-linguistic university students. It shows the importance of this problem for modern foreign language teaching methodology. The author describes elements of sociocultural competence and analyses possible reasons why not enough attention is paid to its control. The author of the article proposes ways of controlling the developments of sociocultural competence, in particular, such of its elements as knowledge, skills, personal capabilities and qualities required for successful cross-cultural communication.